17 Sudden cardiac death and acute myocardial infarction: how has the picture changed?. (9th June 2011) - Mole, G; Watson, D; Davidson, C
Abstract : Introduction: Coronary heart disease (CHD) is a major burden worldwide, particularly in economically developed countries such as the UK. Between 1980 and 2000, deaths from CHD fell by over 50%, and have continued to fall. The cost of CHD manifests itself in mortality, disability and economic impact: this should be looked at in the context of a disease that is preventable. Methods: Data from death certificates and studies with strict clinico-pathological criteria on mortality from CHD were accessed. These were analysed in terms of hospital admissions, revascularisation rates and index of multiple deprivation (IMD). Trends in mortality overall and for different age groups were analysed over time to determine how the picture has changed and predict what may happen going into the future. The mortality rates from the catchment area of the Royal Sussex County Hospital and York Hospital were analysed to assess reliability of official figures against strict clinico-pathological inclusion criteria. A range of statistical tests including, linear regression, ANOVA and JoinPoint regression were employed. Results: Between 1993 and 2008 deaths from CHD have fallen by over 50%. The decline has been greater in older age groups particularly the 65–74 age group (the oldest age group analysed). Comparison with data from studies with strict clinico-pathological criteria showed this to be the age group in which official statistics were least accurate. Regression analysis demonstrated that a higher IMD is associated with increased mortality from CHD (r 2 =0.69, p<0.001). Increased admission rates was not significantly associated with decreased mortality from CHD (r 2 =0.004, p=0.239). Increased revascularisation was significantly associated with decreased mortality from CHD (r 2 =0.99, p<0.001). JoinPoint regression analysis shows a constant rate of decline in mortality from 1993 to 2001 which then decreases faster between 2001 and 2006 before slowing dramatically from 2006 to 2008. JoinPoint regression analysis of different age groups demonstrates that the slower rate of decline from 2006 may be due to stubbornly high numbers of deaths in the 35–44 age group. Lastly the National figures on mortality from CHD are shown to be misleading as many people are still dying from CHD just when they have crossed the 75-year old exclusion criteria; as a result a delay in mortality is presented as prevention of mortality from CHD. Discussion: There is a danger that previous successes are being offset by high rates in the younger cohorts, and that the overall trend may be eventually be reversed. There is still work to be done in reducing risk factors and also applying treatments that have had a proven positive impact (such as revascularisation) more effectively. Statistically significant changes in declining CHD mortality rates. Future work: This 10 000 word report formed the basis of a funding application to the British Heart Foundation for a follow-up to the United Kingdom Heart Attack Study.